Grid-Connected PV System for 324 kW with Improved Maximum PowerPoint Tracking - Abbas Hussein Khariy; Ahmed Rashid Ajel; Sadik Kamel Gharghan; Noaman Mohammad Noaman (Journal of Techniques)
The purpose of this work is to analyze and studded, a grid-connected with a double-stage converter DC/DC, a three-phase five-level inverter system, battery energy system (BESS) with dynamic and static loud. A DC/DC modified boost converter is used to get to most power out of the photovoltaic array along with increasing output voltage. The duty cycle is changed in an incremental conductance maximum power point tracking (MPPT) technique to reach the maximum power point (MMP). In a rotating d-q synchronous reference frame, the multilevel voltage source inverter converts the maximum voltage (VSI). power obtained from first stage power converter (DC-DC) to AC power utilizing a droop controller approach. Finally, the simulation results demonstrated the effectiveness of the proposed modified MPPT strategy for tracking the maximum power under shading conditions with an accuracy of up to 98.5%. The suggested AC controller results also show robust performance for synchronizing with the utility grid with a minimum THD of up to 2.4%.